A speed-endurance training to improve aerobic, anaerobic capacity, and fat oxidation of four groups of athletes - Ramirez, J. M.; Nunez, V. M.; Lancho, C.; Poblador, M. S.; Lancho, J. J. (Medicina dello Sport, 2017)
BACKGROUND: The high-intensity interval training (HIIT) is a type of training characterized by successive short periods of intense activity with short periods of active rest between them. Athletes from different disciplines could highly benefit from speed-endurance training (anaerobic modality of HIIT). The overall aim was to assess the effect of a HIIT protocol (speed-endurance training) on aerobic, anaerobic capacity, and body composition of four groups of athletes (athletics, basketball, cycling and soccer). METHODS: A four group pretest-post-test experimental design was conducted. Forty-four athletes (athletics: N.=12; basketball: N.=8; cycling: N.=11; soccer: N.=13) were evaluated before and after an eight week training program with two weekly sessions of sprint-endurance intervals training at maximum velocity alternating with decreasing active recovery periods (1:2, 1:1, 2:1). VO2, anaerobic threshold (VO2At), BMI, fat mass, and fat free mass were measured. RESULTS: Espirometric post-training measures show an increased aerobic and anaerobic capacity in all groups. VO2 increased between 0.8-6.5%, with greater efficacy in basketball players. VO2At increased between 5.8-9.7%, with no differences between groups. In regards to anthropometric values, a decrease in all body composition outputs has been found, but effect size shows a small experimental relevance. CONCLUSIONS: Decreasing active recovery periods HIIT (speed-endurance training) significantly increases aerobic and anaerobic capacity, as well as improving muscle mechanisms of fat oxidation in all groups of athletes.